Luci della ribalta - Charle Chaplin
Actores: Charles Chaplin, Claire Bloom, Buster Keaton, Melissa Hayden, Mollie Blessing, Barry Bernard, Nigel Bruce, Sydney Chaplin
Area-Película
'1952
Keywords: Genero-Drama